Floral anomalies in Calotropis procera (Aiton) Dryand Natures Bizarre play - Srivastava, Piush; Tripathi, Vineeta; Mishra, Dipak Kumar (Bangladesh Journal of Plant Taxonomy, 2016)
Not available. Bangladesh J. Plant Taxon. 23(1): 79-81, 2016 (June)